Teaching work in multigrade indigenous schools - Glenda Delgado Gastélum; Guadalupe Tinajero Villavicencio (Revista Brasileira de Educação do Campo, 2022)
In this article we analyze the teaching work done by two teachers from northwestern Mexico in a multigrade indigenous school. The indigenous service of Baja California serves mostly children from groups originating from other states of the country who arrived along with their parents, most of them agricultural day laborers, in search of work. From a qualitative approach, the study includes in-depth interviews with two teachers, observation in discussion spaces of the teaching groups and the on-site practice of a teacher during the closure of schools due to the health contingency caused by COVID-19. The findings reveal the organization of the daily teaching activities inherent in multigrade organization, the additional tasks to teaching, the forms of participation promoted by teachers, and the different manifestations and difficulties of their practice. The home education of indigenous teaching, to continue teaching students in rural areas, is the most significant finding.